Timing of predictions in dynamic cheap talk: Experts vs. quacks - Aleksei Smirnov; Egor Starkov (University of Zurich, Department of Economics, 2019)
The paper studies a dynamic communication game in the presence of adverse selection and career concerns. A forecaster of privately known competence, who cares about his reputation, chooses the timing of the forecast regarding the outcome of some future event. We find that in all equilibria in a sufficiently general class earlier reports are more credible. Further, any report hurts the forecaster's reputation in the short run, with later reports incurring larger penalties. The reputation of a silent forecaster, on the other hand, gradually improves over time.
Keywords: C73; D82; D83; D84; 330; career concerns; reputation; dynamic games; games of timing; strategic information transmission